Peran Kurma dalam Meningkatkan Kadar Hemoglobin pada Perempuan: Scoping Review - Kalsum, Umi; Putri, Ayu Syah; Ali, Sarina (Journal of Pharmaceutical and Sciences, 2025)
Iron deficiency anemia (IDA) is a major global health issue that predominantly affects adolescent girls and pregnant women, particularly in developing countries. Dates (Phoenix dactylifera), a natural iron-rich food with essential nutrients, have been proposed as a potential intervention to increase hemoglobin levels. This scoping review aims to explore and evaluate current scientific evidence on the effect of various date varieties in improving hemoglobin levels in women with iron deficiency anemia. Using the Joanna Briggs Institute guidelines, a comprehensive literature search was conducted across ten databases, covering studies from January 2014 to October 2024. Twelve studies meeting the inclusion criteria were analyzed descriptively. The majority reported a significant increase in hemoglobin levels among participants consuming dates, with improvements ranging from 1.18 to 1.67 g/dL. Varieties such as Ajwa, Sukari, and black dates showed notable effectiveness. Some studies also recorded increases in ferritin levels, indicating an improvement in iron reserves. The findings support the use of dates as a beneficial dietary supplement for improving hemoglobin and iron status in women, especially adolescent girls and pregnant women. Further research is necessary to determine optimal dosage and compare the efficacy across different date varieties.